THE EFFECT OF PROBLEM-BASED LEARNING AND DISCOVERY LEARNING MODELS ON STUDENTS CHRITICAL THINKING SKILLS - Nasution, Irma Yuliani; Syafriani, Dewi (Smart Education, 2025)
Abstract: This study aims to determine the effect of the Problem-Based Learning (PBL) model and the Discovery Learning (DL) model on students' critical thinking skills and to identify which aspects of critical thinking are most developed in the topic of reaction rates. The research employed a quasi-experimental design. The sample consisted of two experimental classes: class XI-1 as the first experimental group and class XI-4 as the second, each comprising 34 students. The research instrument was an essay test consisting of three questions. Hypothesis testing was conducted using an Independent Sample T-Test, which yielded a significance value of 0.001. Since the significance value is less than α (0.05), the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, indicating a significant effect of the PBL and DL models on students' critical thinking skills in the topic of reaction rates. The analysis of critical thinking aspects shows that the ability to elementary clarifications was the most developed. This is evidenced by the n-gain percentage, which reached 94% for students taught using the PBL model and 86% for those taught using the DL model. Keywords: Problem-Based Learning, Discovery Learning, Critical Thinking Skills, Reaction Rate Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model Problem Based Learning (PBL) model Discovery Learning (DL) terhadap kemampuan berpikir kritis siswa dan mengetahui aspek berpikir kritis yang paling terkembangkan pada materi laju reaksi. Jenis penelitian ini yaitu quasi experiment. Sampel penelitian terdiri dari XI-1sebagai kelas eksperimen I dan XI-4 sebagai kelas eksperimen II yang masing-masing berjumlah 34 siswa. Instrumen penelitian berupa tes esai sebanyak 3 soal . Uji hipotesis menggunakan uji Independent Sample T-Test dengan hasil penelitian diperoleh harga sig. 0,001. Nilai sig. < α (0,05) sehingga Ha diterima dan Ho ditolak yang artinya terdapat pengaruh yang signifikan kemampuan berpikir kritis siswa yang diberi pembelajaran menggunakan model PBL dan model DL pada materi laju reaksi. Hasil analisis aspek yang diperoleh indikator aspek memberikan penjelasan sederhana adalah aspek kemampuan berpikir kritis yang paling terkembangkan, terlihat dari persentase n-gain 94% untuk yang dijarkan menggunakan model PBL dan 86% untuk yang dijarkan menggunakan model DL. Kata kunci: Problem Based Learning, Discovery Learning, Kemampuan Berpikir Kritis, Laju Reaksi